The seroepidemiologic investigation of bovine adenovirus typel, 2 and 3 (bav-i, 2 and 3) infections in cattle - Sibel Yavru; Atilla Şimşek; Oya Levent (Eurasian Journal of Veterinary Sciences)
In this study, seroprevalence of BAV-1-2-3 infections was investigated in different regions of Turkey. A total of 986 blood sera from cattle in middle (567 blood sera), south (145 blood sera), southeast (176 blood sera) and east Anatolia regions (98 blood sera) were screened for presence of neutralizing antibodies and titers againsl BAV-1,2 and 3 by microneutralization test (mNT). The number of seropositive cattle were 263 (26.67 %) ol 986 for BAV-1, 197 (19,98 %) of 986 for BAV-2 and 190 (19.27 %) of 986 for BAV-3. BAV type 1, 2 and 3 antibodies were observed in 22.05 %, 16.93 % and 19.40 % of 567 blood sera from middle Anatolia; in 31.72 %, 21.38 % and 17.24 % of 145 blood sera from south Anatolia; in 31.25 %, 24.43 % and 20.45 % of 176 blood sera from south-east Anatolia; 37.76 %, 27.55 % and 19.39 % of 98 blood sera from east Anatolia, respectively. Titers of serum neutralizing antibodies were found 1/14.1-1/1260 for BAV-1,1/14.1-1/1060 for BAV-2 and 3. 35.90% of the cattle had antibodies to only one type of BAV. 10.64 % of sera had antibodies to two types of BAV and 2.83 % of sera had antibodies to BAV type 1, 2 and 3. However antibodies to BAV type 1, 2 and 3 were not detected in 50.60 % of 986 sera.